2005
DOI: 10.1002/psc.699
|View full text |Cite
|
Sign up to set email alerts
|

Pediocin‐like antimicrobial peptides (class IIa bacteriocins) and their immunity proteins: biosynthesis, structure, and mode of action

Abstract: Pediocin-like antimicrobial peptides (AMPs) form a group of lactic acid bacteria produced, cationic membrane-permeabilizing peptides with 37 to 48 residues. Upon exposure to membrane-mimicking entities, their hydrophilic, cationic, and highly conserved N-terminal region forms a three-stranded antiparallel beta-sheet supported by a conserved disulfide bridge. This N-terminal beta-sheet region is followed by a central amphiphilic alpha-helix and this in most (if not all) of these peptides is followed by a rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
159
0
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(169 citation statements)
references
References 82 publications
3
159
0
7
Order By: Relevance
“…The immunity proteins of pediocin-like bacteriocins have recently been divided into subgroups A, B and C based on sequence similarities (Fimland et al, 2005). The alignment results between DurB and bacteriocin31-im (BacB) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The immunity proteins of pediocin-like bacteriocins have recently been divided into subgroups A, B and C based on sequence similarities (Fimland et al, 2005). The alignment results between DurB and bacteriocin31-im (BacB) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Its representatives have 37e48 amino acid residues with an N-terminal portion with pleated sheet configuration and a C terminus containing one or two a-helices (Fimland et al, 2005). Pediocin PA-1, which is composed of 44 amino acid residues, isthe only bacteriocin belonging to the subclass IIa that is synthesizednot only by different species, but also by different genera of LAB.…”
Section: Subclass Iiamentioning
confidence: 99%
“…Production of biogenic amines seems to be unfavorable activity of enterococci in fermented dairy products, because biogenic amines have been associated with a number of food poisoning episodes [82]. It has been observed that the prolifi c growth of enterococci in milk and milk products leads to the formation of signifi cant levels of biogenic amines [4,43,83]. In fact, tyramine is the only relevant biogenic amine produced by enterococci isolated from dairy products [84].…”
Section: Undesirable Activities Of Enterococcimentioning
confidence: 99%
“…Enterocins usually belong to the Class II bacteriocins. Enterocins are peptide in nature and are often cationic, amphiphilic, membrane-permeabilizing molecules [3,4]. Bacteriocins may inhibit pathogenic bacteria with a benefi cial impact as protective cultures [3].…”
Section: Introductionmentioning
confidence: 99%